IRON ACQUISITION FROM HYDROUS FE(III)-OXIDES BY AN AEROBIC PSEUDOMONAS SP - Hersman L.; Maurice P.; Sposito G. (My University, 1996)
Iron is a metabolic requirement of living systems, yet iron is very insoluble in aerobic, neutral environments. Therefore, the amount of iron in solution under these conditions is not sufficient to meet the nutrient requirements of microorganisms. It has been assumed that microorganisms acquire iron in these environments through the use of specific iron chelating compounds called siderophores. Interestingly, there is little quantitative data in the literature to support this hypothesis. Our studies were initiated to investigate the mechanism(s) used by an aerobic microorganism to acquire iron from a relatively insoluble iron oxide. When iron was supplied in the form of hematite, a Pseudomonas sp. was able to achieve moderate growth, as compared to growth on FeEDTA. Analysis using high-performance liquid chromatography (HPLC) of the metabolic products of this species showed significant differences between growth on hematite as compared to FeEDTA. The results of these experiments will be discussed in terms of our current knowledge of microbial enhanced iron dissolution, and compared to abiotic dissolution rates.